Catastrophic conditions in couple systems - Lynch, Barbara J (Journal of Couples Therapy, 1999)
A presentation of case studies forms the focus for an exploration of the discovery of an abortion or adoption used as the management of an unwelcome pregnancy which occurred in the context of the marital system. Managing an impasse in the middle phase of therapy in each case led to the emergence of information which then allowed the therapist to work with the couple system to alleviate the core situation out of which presenting problems emanated. In these cases the unwelcome pregnancy had the potential to be cataclysmic to the couple system. Therefore, the possibility that a couple is concealing an abortion or an adoption should be considered by couples' therapists when there is little or no response to usual strategies for change. The reason for concealment is immaterial. What is paramount is that the therapist bring the event to the fore of treatment and work with a couple to put closure on what is generally an unresolved issue. © 1999, by The Haworth Press, Inc. All rights reserved.
Keywords: Abortion; Adoption; Grief; Pregnancy; dept.mft

MFT student training in medical family therapy: A collaborative hospital project with radiation oncology. - Yeager, Barbara; Auyang, Michael; Brown, Dolores L; Dickinson, Patricia; Goldstein, Jayne A; Jaffe, Nina; Mckay, Lynda; Roche, Pamela; Workman, Gwen (Families, Systems, & Health, 1999)
Keywords: dept.mft